VULVAR HYGIENE DURING MENSTRUATION IS ASSOCIATED WITH VULVAR PRURITUS IN ADOLESCENTS - Putri, Kanza; Hartinah, Dewi; Kartikasari, Fitriana ((IJP) Indonesia Jurnal Perawat, 2025)
Vulvar pruritus is a common problem experienced by adolescent  during menstruation, often caused by a lack of understanding of proper vulvar hygiene. Maintaining cleanliness during menstruation significantly impacts one's health, especially in preventing reproductive tract infections. This study aimed to identify the correlation between vulvar hygiene during menstruation and the occurrence of vulvar pruritus among female students at MA Nurul Huda Medini Demak. This quantitative study adopted a correlational research design using a cross-sectional approach. The population of this study consisted of 134 female students at MA Nurul Huda, with a sample of 100 students selected using simple random sampling. Data was collected using an online questionnaire on Google Forms and analyzed using the Spearman rank test and processed using computer software. The results showed a statistically significant correlation between vulvar hygiene during menstruation and vulvar pruritus among adolescent girls at MA Nurul Huda Medini Demak with a p-value of 0.001 α = 0.05, with a moderate strength of association (0.342) and a positive direction. This study concludes that hygiene during menstruation is crucial for maintaining the health of the female reproductive organs, especially to prevent reproductive tract infections such as vulvar pruritus.